Uniqueness of positive solutions for the singular fractional differential equations involving integral boundary value conditions - Min, D.; Liu, Lishan; Wu, Yong Hong (SpringerOpen, 2018)
© 2018, The Author(s). This paper is concerned with the uniqueness of positive solutions for a class of singular fractional differential equations with integral boundary conditions. The nonlinear term and boundary conditions of fractional differential equation contain the fractional order derivatives. The uniqueness of positive solutions is derived by the fixed point theorem of mixed monotone operator. An example is given to demonstrate the validity of our main results.